2001
DOI: 10.1074/jbc.m101106200
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Thermoalkalophilic Hydrolase of Paucimonas lemoignei with High Specificity for Amorphous Polyesters of Short Chain-length Hydroxyalkanoic Acids

Abstract: A novel type of hydrolase was purified from culture fluid of Paucimonas (formerly Pseudomonas) lemoignei. Biochemical characterization revealed an unusual substrate specificity of the purified enzyme for amorphous poly((R)-3-hydroxyalkanoates) (PHA) such as native granules of natural poly((R)-3-hydroxybutyrate) (PHB) or poly((R)-3-hydroxyvalerate) (PHV), artificial cholatecoated granules of natural PHB or PHV, atactic poly((R,S)-3-hydroxybutyrate), and oligomers of (R)-3-hydroxybutyrate (3HB) with six or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(152 citation statements)
references
References 46 publications
3
146
0
3
Order By: Relevance
“…Recently, amorphous PHB-specific extracellular PHB depolymerase was found from Paucimonas lemoignei (PhaZ7 ple ) (9). Although PhaZ7 ple show a high PHB-hydrolyzing specific activity, the amino acid sequence was not similar to either the type I or type II catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, amorphous PHB-specific extracellular PHB depolymerase was found from Paucimonas lemoignei (PhaZ7 ple ) (9). Although PhaZ7 ple show a high PHB-hydrolyzing specific activity, the amino acid sequence was not similar to either the type I or type II catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
“…The deduced amino acid sequence showed 45 to 50% sequence identity with mesophilic Bacillus family I-4 lipases (3,18,21,34), ϳ20% sequence identity with thermophilic Bacillus family I-5 lipases (2,11,29), but no identity with PHA depolymerase from P. lemoignei, except for the conserved pentapeptide (6). Functional expression and purification of the recombinant enzyme in E. coli.…”
Section: Resultsmentioning
confidence: 99%
“…The PHA depolymerase from P. lemoignei, PhaZ7, is included in the lipases possessing an Ala-His-SerMet-Gly pentapeptide. Because of its unique sequence, Handrick et al suggested that PhaZ7 should be classified into a new family of carboxylesterases (6). The purified recombinant PLA depolymerase could not degrade P(HB-co-HV) ( Table 2), and the entire amino acid sequences of PlaA and PhaZ7 were different, except for the catalytic pentapeptide.…”
Section: Discussionmentioning
confidence: 99%
“…Semicrystalline dPHB was isolated from accumulating cells of R. eutropha H16 by sodium hypochlorite digestion and subsequent solvent extraction of the dried polymer with acetone-diethyl ether (2:1). nPHB granules with an intact surface layer were prepared from crude extracts (French press) of PHB-rich cells of R. eutropha H16 or from recombinant E. coli harboring the PHB biosynthetic genes phaCBA of R. eutropha with or without phaP (17) by two sodium phosphate-buffered glycerol density gradient centrifugation steps as described previously (10). nPHB granules were isolated from PHB-accumulating cells of Chromobacterium violaceum, Bacillus megaterium, Bacillus cereus, and R. rubum by the same procedure.…”
Section: Methodsmentioning
confidence: 99%